1998
DOI: 10.1111/j.1471-0528.1998.tb10237.x
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind, randomised trial comparing the effects of tibolone and continuous combined hormone replacement therapy in postmenopausal women with menopausal symptoms

Abstract: Objective To compare the effects of two postmenopausal regimens on menopausal symptoms, bleeding episodes, side effects and acceptability.Design Double-blind, randomised controlled trial.Setting Twenty-nine sites in Denmark, nine in Norway and six in Sweden.Participants Four hundred and thirty-seven postmenopausal women with menopausal complaints. None of these women had had a hysterectomy.Interventions Daily treatment with tibolone 2.5 mg (n = 218) or l7p-oestradiol 2 mg plus norethisterone acetate 1 mg (E,lN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(54 citation statements)
references
References 41 publications
2
50
0
2
Order By: Relevance
“…3a-and 3b-Hydroxytibolone are the main metabolites in the circulation with a half life of about 7 h, and are responsible for the eŠectiveness of tibolone in alleviating climacteric symptoms and prevention of bone loss. 110) Tibolone and 7a-methylnorethisterone have produced similar inhibition of aromatase activity, 58% and 65%, respectively, to those obtained from MCF-7 cell study. 111) Venlafaxine Venlafaxine is a phenethylamine bicyclic anti-depressant.…”
Section: Citaloprammentioning
confidence: 55%
“…3a-and 3b-Hydroxytibolone are the main metabolites in the circulation with a half life of about 7 h, and are responsible for the eŠectiveness of tibolone in alleviating climacteric symptoms and prevention of bone loss. 110) Tibolone and 7a-methylnorethisterone have produced similar inhibition of aromatase activity, 58% and 65%, respectively, to those obtained from MCF-7 cell study. 111) Venlafaxine Venlafaxine is a phenethylamine bicyclic anti-depressant.…”
Section: Citaloprammentioning
confidence: 55%
“…Urogenital system: We found two RCTs. The first RCT found no significant difference between tibolone and combined hormonal treatment in terms of subjective reports of vaginal lubrication; both interventions improved lubrication compared with baseline 28. The second RCT (437 women) found that tibolone improved sexual satisfaction compared with oestradiol plus norethisterone (P<0.05) 31.…”
Section: Benefitsmentioning
confidence: 98%
“…Vasomotor symptoms: We found three RCTs, two of tibolone versus continuous combined oestrogen/progestogen treatment over 48 and 52 weeks (672 women with menopausal symptoms) 28 29 and one versus placebo over 16 weeks (82 women with menopausal symptoms) 30. The first RCT found a slightly greater reduction in hot flushes with the combined regimen than with tibolone over 48 weeks (P=0.01).…”
Section: Benefitsmentioning
confidence: 99%
“…In addition, T is locally converted into the D 4isomer by 3b-OH steroid dehydrogenase isomerase, which prevents endometrial proliferation and hyperplasia; finally, it stimulates sulphotransferase enzymes and induces the inhibition of sulphatase, causing a further reduction in estrogenic activity in the endometrium [5,83]. The International Tibolone Consensus Group highlighted the good profile of tolerability which is associated with a better vaginal bleeding control as compared to EPT, especially in the first 6 months of therapy [1].…”
Section: Endometrial Cancermentioning
confidence: 99%